Adolescents' perspectives on relationships with grandparents: The contribution of adolescent, grandparent, and parent–grandparent relationship variables - Shalhevet, Attar Schwartz; Tan, Jo Pei; Buchanan, Ann (Elsevier, 2009)
There is limited research on adolescent–grandparent relationships, especially from the adolescent perspective and on large-scale samples. The study examined the associations between the adolescent–grandparent relationship (i.e., importance of, emotional closeness to, and respect for grandparents' views) and the characteristics of the adolescent, grandparent, and parent–grandparent relationship, as well as the interactions between several of these factors. It was based on a representative sample of 1478 students aged 11–16 from England and Wales who completed a structured questionnaire. Results supported the position that grandparents are a significant factor in the lives of adolescents. Findings of hierarchical regression analyses showed that more frequent contact, greater grandparent involvement, and better parent–grandparent relationships predicted adolescents' reports on higher levels of emotional closeness to, importance of, and respect for their closest grandparent's views. The interactions consistently emphasized the role of parents as gatekeepers of intergenerational exchange.